2008
DOI: 10.1097/aln.0b013e31817881e1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Analgesia by Oral Standardized Cannabis Extract on Acute Inflammatory Pain and Hyperalgesia in Volunteers

Abstract: To conclude, no analgesic or antihyperalgesic activity of cannabis extract was found in the experiments. Moreover, the results even point to the development of a hyperalgesic state under cannabinoids. Together with previous data, the current results suggest that cannabinoids are not effective analgesics for the treatment of acute nociceptive pain in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 46 publications
(51 reference statements)
6
101
1
Order By: Relevance
“…However, it must be borne in mind that the reduced pain sensitivity in CB1 receptor-deficient mice and the analgesic action of CB1 receptor antagonists is limited to activity-dependent pain sensitization and has not been observed in inflammatory or neuropathic pain models. This is supported by findings from acute human pain models [15,22], as well as from clinical studies in postoperative pain patients. In these settings, cannabinoids not only failed to show an analgesic effect, but instead resulted in increased pain.…”
Section: Disinhibition Following Nociceptor Stimulationsupporting
confidence: 67%
“…However, it must be borne in mind that the reduced pain sensitivity in CB1 receptor-deficient mice and the analgesic action of CB1 receptor antagonists is limited to activity-dependent pain sensitization and has not been observed in inflammatory or neuropathic pain models. This is supported by findings from acute human pain models [15,22], as well as from clinical studies in postoperative pain patients. In these settings, cannabinoids not only failed to show an analgesic effect, but instead resulted in increased pain.…”
Section: Disinhibition Following Nociceptor Stimulationsupporting
confidence: 67%
“…In view of these attributes, we have argued that assays of pain-depressed behavior may complement conventional assays of pain-stimulated behavior and increase the predictive validity of preclinical candidate analgesic assessment (Negus et al, , 2010a. Given the poor efficacy of THC and other cannabinoid receptor agonists to treat acute pain in humans (Raft et al, 1977;Buggy et al, 2003;Naef et al, 2003;Beaulieu, 2006;Kraft et al, 2008;Klooker et al, 2011) we predicted that THC and CP55940 would not produce antinociception in assays of acute pain-depressed behavior in rats despite the apparent efficacy of these drugs in standard assays of pain-stimulated behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Results with THC and CP55940 have illustrated this discordance insofar as cannabinoid agonists produce robust and reliable antinociception in most assays of acute pain-stimulated behavior but little or no analgesia against acute pain in humans (Rice, 2006;Karst et al, 2010;Kraft, 2012). For example, oral delivery of THC or other cannabinoids lacked analgesic efficacy or exacerbated pain in most well controlled clinical studies of postoperative or acute experimental pain (Raft et al, 1977;Buggy et al, 2003;Naef et al, 2003;Beaulieu, 2006;Kraft et al, 2008;Klooker et al, 2011); for the lone exception, see Campbell et al (2001). Likewise, smoked marijuana at doses up to those producing untoward motor/cognitive/subjective effects produced little or no change in sensitivity to acute thermal, mechanical, or chemical noxious stimuli in clinical laboratory studies, and as with oral cannabinoids, pain ratings were sometimes worsened by smoked cannabis (Greenwald and Stitzer, 2000;Wallace et al, 2007).…”
mentioning
confidence: 99%
“…Clinical studies have demonstrated the analgesic effectiveness of cannabinoids including marijuana and dronabinol in neuropathic pain populations (Svendsen et al, 2004;Abrams et al, 2007;Nurmikko et al, 2007;Wilsey et al, 2008;Ellis et al, 2009;Ware et al, 2010). However, the cannabinoids proved to be less effective in attenuating other pain modalities; dronabinol (5 mg) failed to decrease postoperative pain (Buggy et al, 2003) and sensitivity to a thermal stimulus (Roberts et al, 2006), and a higher dronabinol dose (20 mg) failed to reduce acute inflammatory pain, hyperalgesia (Kraft et al, 2008), or increase pain threshold in a pressure test (Naef et al, 2003). Although dronabinol did not produce analgesia in these experimental pain models, a single study successfully demonstrated the effectiveness of smoked marijuana in reducing sensitivity to radiant heat stimulation (Greenwald and Stitzer, 2000).…”
Section: Discussionmentioning
confidence: 99%